Clinical Manual of Fever in Children (Springer International Publishing, 2018)
The book covers all the different types of fever and its possible complications discussed the management of fever with guidelines on antipyretics and their side effects and differential diagnosis of fever, with problem-setting and solving as a case presentation. The second edition of this well-received book has been fully updated to include exciting new information of the pathogenesis of fever, including functions of interleukin and all the latest guidelines from NICE and Cochrane Library, as well as all the most up-to-date information and guidelines on febrile seizures. This reader-friendly reference on the disorders of body temperature in children covers the entire spectrum of subjects related to fever. It gives an overview of the best treatment options in order to achieve the best results. Containing a core message at the start of each chapter and with and a reader-friendly format this is an indispensable guide for paediatr icians, family doctors and other professionals who are regularly consulted because of febrile children. .